Abnormal Expression Pattern of the IL-2 Receptor β-Chain on CD4+ T Cells in ANCA-Associated Vasculitis. (9th February 2014) - Wilde, Benjamin; Hoerning, André; Kribben, Andreas; Witzke, Oliver; Dolff, Sebastian
Abstract : Background/Aim . ANCA-associated vasculitis (AAV) is a small-vessel vasculitis of autoimmune origin. In addition to autoantibodies, T cells have a pivotal pathophysiological role in this disease. T-cell homeostasis and immune tolerance critically depend on IL-2 and its receptor expressed by T cells. In this study, we investigated the IL-2 receptor (IL-2r) expression on CD4 + T cells in AAV. Methods . Thirty patients with AAV and 15 age-matched healthy controls (HC) were enrolled. T cells from peripheral blood were analysed by flow cytometry for expression of the IL-2r α - and β -chain. Results . The IL-2r α -chain was overexpressed in AAV as compared to HC (36 ± 16 % versus 20 ± 9 %, P < 0.005 ). The IL-2r- β -chain expression was significantly reduced on CD25 + CD4 + T-cells and CD4 + CD25 + FoxP3 p o s regulatory T-cells (Tregs; AAV versus HC: 48 ± 14 % versus 62 ± 9 %, P = 0.002 and 38 ± 18 % versus 68 ± 5 %, P = 0.002 ). Low β -chain expression in AAV was associated with relapsing disease and systemic vasculitis with renal involvement. Conclusion . The IL-2r expression pattern is abnormal in AAV. To our knowledge, we are the first to show that the β -chain expression is drastically diminished on T cells in AAV and related to a less favorable disease course. Given the indispensable function of the β -chain in IL-2 signaling of T cells, diminished expression may contribute to disturbed immune homeostasis in AAV.